The current situation of e-books in academic and public libraries in Sweden (Libellarium: journal for research in the field of information and related sciences, 2014)
Introducing e-books into Swedish libraries has been influenced by the idea of equal access to all media for all Swedish citizens as well as by librarians’ wish to provide the best possible service to their users. Libraries perceived this new resource and service as a way of fulfilling their specific function in a democratic society, which is usually described as mediation (or transfer) of knowledge and culture to all. This is a common basis for the incorporation of new media and information resources (including e-books) into Swedish academic and public libraries. Apart from this common platform, we see other similarities in working with e-books in both types of libraries, but also a number of differences. Most of them relate to the position of libraries within their respective context and in relation to their specific role. Academic libraries are quite influential players in the global scholarly communication and supporters of both research and study processes. As such they are embedded in a mainly international market of scientific information and scholarly materials. They have significant resources provided by their parent universities for the acquisition of scholarly material and a wide choice of commercially available material from different providers. They are also incorporated into a national library consortium with great negotiation power. Thus, they have more freedom to experiment with a variety of business and pricing models offered on the international market. They also have a high competence in publishing and are often publishers themselves. Their involvement in research processes and in open access initiatives puts them in a position to provide expertise to researchers in the areas of publishing and intellectual property protection. Public libraries are part of the local cultural and educational landscape. As such, they depend on the production of media and content in national languages which helps cater to the needs and demands of the local population. They are also customers on the limited market of publishing, entertainment and education-related materials which help fulfil their function as educators. As public libraries offer open and free access to their resources to the entire population of a certain area, eventually covering the whole country, they are regarded as a disruptive element in the market economy. This perceived threat from public libraries was reborn with the emergence of e-books. Despite their differences, both academic and public libraries face similar challenges and problems relating to the management of their collections, creating metadata, and providing access to their content. So far, there haven’t been any mutually satisfactory solutions.
Keywords: e-books; academic libraries; public libraries; e-books distribution; Sweden